Ritual em Richard Schechner e Victor Turner: aspectos de um diálogo interdisciplinar - Costa, Grasielle Aires da (2015)
This work aims to analyze the concepts of ritual developed by Richard Schechner and Victor Turner. This is realized through the definition, analysis and discussion of the concepts looking for the dialog between Schechner and Turner. The research was developed by reading and analysing the major volumes published by these authors, what is Schism and Continuity; Forest of Symbols; The Ritual Process; Dramas, Fields and Metaphors and From Ritual to Theater by Turner and made by Schechner Environmental Theater; Essays on Performance Theory; Between Theater and Anthropology; The Future of Ritual and Performance Studies. Was not found any work like this. It is an inedited and presented an important review on Schechner‟s and Turner‟s written. The ritual concept needs this multiplicity look to take a new breath and look up different sea-lines. This job has a methodological richness because points out precisely the fact that the research belongs analyse the field "between" the theatre and anthropology. It is not remand to any discipline and the same time belongs to all of them. This is a bibliographic study what can provide theoretical support for various research fields.